Implication of Climate Variability on Water Resources Availability and Management of Melamchi Municipality - Baral, Samikshya; Bhandari, Anil (The Batuk, 2026)
This study examines the impact of climate change on water resources in Melamchi Municipality, Nepal, based on focus group discussions, interviews, and field observations. Thirty-one years (1990–2021) of temperature and precipitation data from DHM were analyzed using the Mann-Kendall test, Sen's slope, and autocorrelation analysis. The study assessed the community's vulnerability to climate change using the exposure, sensitivity, and adaptive capacity indicators. The result indicates rising temperature at all stations while precipitation records indicate a significant decreasing trend in eight of the twelve stations. Autocorrelation analysis and Box-Ljung test of Dubachaur station precipitation indicated that the rainfall in a specific year is strongly related to the rainfall in subsequent years, while the yearly temperature data of the Melamchi region exhibited no strong linear dependencies and confirmed the absence of significant autocorrelations. Vulnerability analysis revealed differential exposure, sensitivity, and adaptive capacity within municipality according to the availability of sources. To address the issue, the study highlights the urgent need for adaptive water management strategies that incorporate both scientific and traditional knowledge.